Answer:
4^x - 2^(x+1) = 48
x=3
Step-by-step explanation:
Answer:
the answer is -7
please mark this as brainliest
<span>1.Describe how the graph of y = x2 can be transformed to the graph of the given equation.
y = (x+17)2
Shift the graph of y = x2 left 17 units.
2.Describe how the graph of y= x2 can be transformed to the graph of the given equation.
y = (x-4)2-8
Shift the graph of y = x2 right 4 units and then down 8 units.
.Describe how to transform the graph of f into the graph of g.
f(x) = x2 and g(x) = -(-x)2
Reflect the graph of f across the y-axis and then reflect across the x-axis.
Question 4 (Multiple Choice Worth 2 points)
Describe how the graph of y= x2 can be transformed to the graph of the given equation.
y = x2 + 8
Shift the graph of y = x2 up 8 units.
Question 5 (Essay Worth 2 points)
Describe the transformation of the graph of f into the graph of g as either a horizontal or vertical stretch.
f as a function of x is equal to the square root of x and g as a function of x is equal to 8 times the square root of x
f(x) = √x, g(x) = 8√x
vertical stretch factor 8
Plz mark as brainlest</span>
Answer:
Let the number to find be x
7 - 9x = 52
-9x = 52-7
- 9x = -45
Divide by - 9
x = 5
The number is 5
Hope this helps.